Trauma-induced coagulopathy: prospective observation study - Vyshynska, Mariana (ScienceRise: Medical Science, 2021)
Coagulopathy remains the leading cause of illness and death in people with severe trauma. The aim was to study the indicators of vascular-platelet hemostasis in severe trauma and to establish changes in the main pathophysiological mechanisms of primary hemostasis that occur in patients with trauma-induced coagulopathy, compared with almost healthy individuals of the same age. Materials and methods. The study included 44 patients aged 19 to 55 years (36.1 [28.7; 43.2] years). The control group included 20 patients of the therapeutic department without preconditions for changes in the hemostasis system, and the main group - 24 patients with diagnosis of “severe trauma” who were treated in the anesthesiology and intensive care department. Results and discussion. We studied indicators of intravascular platelet activation. Patients had a normal number of platelets in the venous blood, but the level of spherocytes and spheroechinocytes increased. On the 3rd day after the injury, number of platelets in the venous blood was normal, however the level of discocytes decreased, and the level of discochinocytes, spheroechinocytes and the sum of active forms of platelets increased. On the fifth day, the level of discochinocytes and active forms of platelets, significantly higher (p<0.05) among patients of the main group, and spherocytes, spheroechinocytes and platelets involved in the aggregates, were significantly lower than in the control group of patients (p<0.05). Conclusions. Indicators of vascular-platelet hemostasis in patients with polytrauma had significant differences from those of the control group. This may be evidence of activation of the vascular-platelet system of the hemostasis system and may be a prerequisite for late thrombotic complications in patients with polytrauma